Characteristics of Mexican women admitted to emergency care units: alcohol consumption and related problems Características de mujeres mexicanas que asisten a servicios de urgencias: consumo de alcohol y problemas relacionados - Martha Romero; Liliana Mondragón; Cheryl Cherpitel; Ma. Elena Medina-Mora; Guilherme Borges (Instituto Nacional de Salud Pública, 2001)
Objective. This article describes the demographic characteristics and psychological differences in a sample of female heavy and non-heavy drinkers who attended three emergency services of the Mexican city of Pachuca, Hidalgo. Material and Methods. A sample of patients seen at emergency services (ES) patients over the age of 18 was selected using ES admission forms. Twenty-five-minute, face-to-face interviews were conducted by a group of trained interviewers. Patients answered various questionnaires and scales to measure alcohol consumption and to provide information on variables that have proved to be related to female drinking. Results. Thirty-six women (5.2%) out of 717 of the total number of women were found to be heavy drinkers according to the TWEAK scale. This group of women had 2.3 times the risk of becoming depressed, 2.87 times the risk of taking other drugs, 1.95 times the likelihood of having been sexually abused and 1.57 times the risk of displaying suicidal ideation. Conclusions. Data from this small analysis confirm international findings that problem drinking among females throughout the life cycle is linked to depression. As regards the screening instruments employed, it is necessary to conduct more in-depth research to enrich their contents and increase their reliability and validity when used among female populations. In this study, the TWEAK proved to be extremely useful for studies in emergency services. The English version of this paper is available too at: http://www.insp.mx/salud/index.html Objetivo. El presente artículo de investigación describe las características demográficas y las diferencias psicológicas en una muestra de mujeres con consumo alto y consumo no-alto de alcohol, que asistieron a tres servicios de urgencias localizados en la ciudad mexicana de Pachuca, Hidalgo. Material y métodos. Una muestra de las pacientes mayores de 18 años que asistieron al servicio de urgencias fue seleccionada utilizando las formas de admisión. Se hicieron entrevistas cara a cara de 25 minutos de duración por un grupo de entrevistadores capacitados. Las pacientes contestaron diferentes instrumentos para medir el consumo de alcohol y escalas de otras variables que se sabe pueden relacionarse con el consumo femenino de alcohol. Resultados. Treinta y seis mujeres (5.2%) de un total de 717 fueron calificadas como bebedoras con consumo alto de alcohol de acuerdo con la escala de TWEAK. Presentaron 2.3 veces mayor riesgo de estar deprimidas, 2.87 de consumir otras drogas, 1.95 de haber sido víctimas de abuso sexual y 1.57 de presentar ideación suicida. Conclusiones. Los resultados de la investigación confirman que el consumo de alcohol en las mujeres a lo largo del ciclo vital está ligado a la depresión. En relación con los instrumentos de tamizaje utilizados, es necesario conducir mayor número de investigaciones en profundidad para enriquecer sus contenidos y aumentar su confiabilidad y validez al utilizarlos con poblaciones femeninas. En este estudio, el TWEAK probó ser de gran utilidad para su uso en los estudios de los servicios de emergencia. El texto completo en inglés de este artículo también está disponible en: http://www.insp.mx/salud/index.html